Nomenclature and taxonomy of Terarista fujiana (Diptera: Psilidae) - Zhou, Jiale; Evenhuis, Neal L.; Yang, Ding (Zootaxa, 2022)
The nomenclature and taxonomy of Terarista fujiana Wang, 1999 are reviewed and discussed, resulting in the following new synonymy and new combination: Loxocera Meigen, 1803 s. str. = Terarista Yang & Wang, 2003, syn. nov.; L. (L.) fujiana (Wang, 1999), comb. nov. Terarista Wang, 1999 is treated as a nomen nudum.